+0  
 
0
71
1
avatar

(¬p V ¬q V r) → ¬ (q V r)

Guest Sep 21, 2017
Sort: 

1+0 Answers

 #1
avatar+18612 
+2

Simplify the following logical expression using the Laws of Logic.

 

(¬p ∨ ¬q V r) → ¬ (q ∨ r) = ¬r ∧ ( p ∨ ¬q )

 

 

 

laugh

heureka  Sep 22, 2017

28 Online Users

avatar
avatar
avatar
avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details